Hi,
to Q1:
the brackets are not necessary. Collect like terms:
7t^(-6)*(-3)t^(-3)*c^(-3) = -21t^(-9)*c^(-3)
to Q3.:
11x + 6y = 153
156 = -3y + 10x ==> 156 - 10x = -3y ==> -312 + 20x = 6y
Now plug in the term for 6y into the first equation:
11x + (-312 + 20x) = 153
31x = 465
x = 15 plug in this value into the second equation to calculate y:
6y = -312 + 20*15 = -12
y = -2
EB
Hello, radioflyer01!
Solve using the elimination method.
. . 11x + 6y .= .153
. . 156 .= .-3y + 10x
We have: .11x + 6y .= .153 . [1]
. . . . . . . .10x .- 3y .= .156 . [2]
Multiply [2] by 2: .20x - .6y .= .312
. . . . . . Add [1]: .11x + 6y .= .153
. . And we have: .31x = 465 . → . x = 15
Substitute into [1]: .11(15) + 6y .= .153 . → . y = -2